2020
DOI: 10.1101/2020.11.13.381202
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictive attenuation of touch and tactile gating are distinct perceptual phenomena

Abstract: In recent decades, research on somatosensory perception has led to two important observations. First, self-generated touches that are predicted by voluntary movements become attenuated compared to externally generated touches of the same intensity (attenuation). Second, externally generated touches feel weaker and are more difficult to detect during movement compared to rest (gating). Researchers today often consider gating and attenuation to be the same suppression process; however, this assumption is unwarra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 130 publications
(349 reference statements)
3
23
0
Order By: Relevance
“…Our results are incompatible with the idea that suppression of external probe stimuli is due to an unspecific gating mechanism that is caused by peripheral reafferences, independent of sensorimotor predictions. 5,7 Although a general gating mechanism could explain the observed suppression in all four movement conditions compared to rest, it cannot account for differences between congruent and incongruent conditions. This congruency effect cannot be attributed to differences in the movement either, 16,31,32 as kinematic behaviour was similar between the conditions.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Our results are incompatible with the idea that suppression of external probe stimuli is due to an unspecific gating mechanism that is caused by peripheral reafferences, independent of sensorimotor predictions. 5,7 Although a general gating mechanism could explain the observed suppression in all four movement conditions compared to rest, it cannot account for differences between congruent and incongruent conditions. This congruency effect cannot be attributed to differences in the movement either, 16,31,32 as kinematic behaviour was similar between the conditions.…”
Section: Discussionmentioning
confidence: 92%
“…between predictable and unpredictable sensory states, but instead cancels out any tactile probes arising on the moving limb. 5,7 Despite evidence that a movement-induced reduction in tactile sensitivity is accompanied by a downregulation of neural activity in the primary somatosensory and motor cortices already before movement onset, 8 whether and how this phenomenon is related to prediction and expresses itself on the perceptual level is still obscure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, electrophysiological responses to median nerve stimulation are suppressed to a greater extent during action execution than action observation (Hari et al 1998), the spectral power is differentially modulated for action observation and action execution (Cochin et al 1999;Silas et al 2010) (see also (Waldert et al 2015)) and the corticospinal excitability effects observed during action observation (Fadiga et al 1995;Gueugneau et al 2015) might be weaker or less related to action execution (Bunday et al 2016;Hannah et al 2018) than theorized by the directmatching hypothesis. In the present study, we quantified somatosensory attenuation, a robust phenomenon manifested during voluntary action (Bays et al 2005;Kilteni et al 2020) that is theorized to result from the predictions of the internal forward models (Wolpert and Ghahramani 2000;Blakemore et al 2000;Bays and Wolpert 2008) and not from generalized gating processes (Kilteni and Ehrsson 2020b). We have used this specific experimental approach in a previous study that investigated whether motor imagery includes simulation processes similar to those during action execution (Kilteni et al 2018).…”
Section: Discussionmentioning
confidence: 98%
“…In each condition, we fitted the participants' responses with a generalized linear model using a logistic function (Equation 1), similar to previous studies (Bays et al 2005(Bays et al , 2006Kilteni et al 2019Kilteni et al , 2020Kilteni and Ehrsson 2020b). Two parameters of interest were extracted: the point of subjective equality (PSE), which represents the intensity at which the test tap felt as strong as the comparison tap (p = 0.5) and which quantifies the attenuation, and the just noticeable difference (JND), which reflects the participants' sensitivity in force discrimination.…”
Section: Discussionmentioning
confidence: 99%